Tommye Dean: capstone - Dean, Tommye, artist (Colorado State University. Libraries, 2019)
The artist's statement: My work is a representation of my beliefs, interests, and way of seeing the world. These influences change often as I come into contact with new experiences. Meaning my work is constantly changing. I draw inspiration from everything around me including my peers, architecture, color etc. Sometimes the pattern on a carpet or color of a fruit can give me a great idea for a project, so I pay close attention to my surroundings waiting for the next time an idea strikes. I love to bounce ideas off of my friends and see where their minds take them. Everyone experiences the world differently, therefore I find it very useful to see what sparks an interest in someone or gets them excited. In the end design is for people so the more eyes I can get a piece in front of the better. My work tends to change with my mood, ranging from dark and grungy to colorful and animated. This lends to an interesting variety of work I've created. Overall I'd say my work keeps a general tone of playfulness with a simplistic modern overlay. I like to use a broad spectrum of mediums to bring my designs to completion. I frequently incorporate my photography into designs either as a main element or to break apart into separate pieces. I find it easier to not limit myself when it comes to materials and to think of my work as whatever I need it to be. I'm very specific about my process of working with a client, I meet with them and make sure that I understand their needs fully and what their hopes are from me. I find it best to start with a mood board that works as a brainstorming process to understanding how I want the audience to feel and who this is for. This is an important part of my process because if my final product reflects the feel of my original mood board then I was successful in my design. I find producing an excess of ideas at the beginning is a great way to get out everything I can think of so that I can narrow down after and end with the best ideas. This process has led to many great designs and happy clients.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design